Global scheduling model for trackless rubber-tyred vehicle in underground coal mines - CHEN Xiangyuan; PAN Tao; ZHOU Bin (Gong-kuang zidonghua, 2023)
There are a large number of trackless rubber-tyred vehicles in underground coal mines. The transportation is easily affected by moving surfaces, emergencies, and other factors. Traditional manual scheduling methods are inefficient and prone to problems such as idle, empty, and wasted vehicles. However, existing auxiliary transportation vehicle scheduling methods mostly focus on fixed tasks using discrete event optimization schemes. It breaks down the global model into local models, and lacks analysis of the overall situation of underground coal mines. In order to solve the above problems, a global scheduling model for trackless rubber-tyred vehicle in underground coal mines based on Baidu industrial solver is proposed. The design scheme of the information collection module, data modeling module, and industrial solver module in this model are introduced, as well as the global scheduling process for trackless rubber-tyred vehicles. This model adopts a global scheduling algorithm for trackless rubber-tyred vehicles based on 'batch solving and iterative optimization'. The vehicle scheduling problem is optimized and solved by Baidu industrial solver based on action adjust heuristic algorithm. It solves the problems of long solving time and easy getting stuck in local optimal solutions in traditional scheduling models. The experimental results show that the global scheduling model for trackless rubber-tyred vehicles based on Baidu industrial solver significantly reduces the number of vehicles used and improves vehicle operation efficiency compared to manual scheduling methods. The solution time for scheduling optimization is lower than that of the local scheduling model based on Gurobi solver. It is more suitable for large-scale complex scheduling tasks in underground auxiliary transportation scenarios.